Study of the relationship between gastroesophageal reflux disease, bruxism and erosive lesions of hard dental tissues in the practice of dentists - Bida В. І.; Doroshenko М. М. (Actual Dentistry, 2024)
Introduction. A recent study found a relationship between bruxism, gastroesophageal reflux disease (GERD), and tooth loss, which may act in concert to attack tooth hard tissue both chemically (reflux) and mechanically (bruxism). Because bruxism is closely associated with symptomatic GERD, and patients with frequent bruxism symptoms tend to have GERD for long periods of time, dentists should consider assessment of GERD status as an integral part of the medical evaluation of bruxism, especially severe bruxism. The purpose of the study. To study the relationship between confirmed gastroesophageal reflux disease (GERD), bruxism, and erosive lesions of hard dental tissues in 119 patients aged 25–65. Research methods. 119 patients with confirmed GERD who applied to the Department of Orthopedic Stomatology, Digital Technologies and Implantology of the P. L. Shupyk National Hospital of Ukraine during 2021–2024 for the purpose of orthopedic treatment of the loss of hard tooth tissues took part in the study. Group 1 included 56 patients with a non-erosive form, and group 2–63 people with an erosive form of GERD. In turn, each of the research groups was further divided into subgroups A and B. Subgroup A included patients with a course of GERD up to 5 years, subgroup B — with a course of GERD more than 5 years. The control group included 17 patients without somatic pathology with a healthy oral cavity. The degree of loss of hard dental tissues was performed using the tooth wear index (TWI), a d the assessment of the quality of life o patients with GERD and lesions of hard dental tissues was performed according to the OHIP-14 questionnaire (Oral Health Impact Profile). Statistical data analysis was performed using the STATISTICA program (StatSoft Inc., Tulsa, Oklahoma, USA). The results. In patients diagnosed with GERD, bruxism was found in 58.9% of patients of the 1st group and 73.0% of the 2nd group. At the same time, in most cases in both groups, bruxism was detected in subgroups with GERD lasting more than 5 years. A slight loss of hard tissues was determined mainly in patients with GERD up to 5 years of age (3.6% in group 1 and 6.4% in group 2, respectively). The majority of patients of both groups with the course of GERD up to 5 years had a tooth wear index equal to 2 (30.4%—in the 1st and 19.0%— in the 2nd). At the same time, with a long course of GERD, 30.4% of patients of the 1st group and 23.8% of patients of the 2nd group had pronounced loss of hard tissues of the teeth (IRR = 3). Complete loss of enamel with exposure of the pulp and exposure of secondary dentin was found in 12.5% of patients of the 1st group with a course of GERD for more than 5 years, in 25.4% of the 2nd (6.4% in subgroup A and 19%—in subgroup B). According to all questions of the OHIP questionnaire, 14 patients with an erosive form and a long course of GERD had significantly worse indicators. Conclusion. We determined the connection between GERD, bruxism, and erosive damage to the teeth. GERD was associated with all types of bruxism with different odds ratios. Long-term GERD led to pronounced loss of hard dental tissues (IRR = 3). It is necessary to emphasize the need for a multidisciplinary approach to treating patients in this category because somatic pathology can hide dental pathology, and vice versa.